Identificação de grupos heteróticos entre gerações F2 de híbridos simples de milho para segunda safra - Silva, Arthur Pereira da [UNESP] (2015)
Using F 2 generations of single-cross hybrids, with efficient exploitation of heterosis, can contribute significantly to increase corn grain yield, either through direct use or extraction of new lines and obtaining new hybrids. This study aimed toidentifyF 2 generations of single-cross hybrids for these purposes, for the second season crop. The 66 hybrids from 12 F 2 parentals resulted of a complete diallel and four checks were evaluated in a quadruple lattice 9x9 experimental design and analyzed according to Gardner and Eberhart diallel analysis. The following traits were evaluated: female flowering (FF), plant height (AP), ear height (AE), general disease note (ND), lodged plants plus broken (AQ), prolificacy (PR) and grain yield (RG), Selvíria-MS, second crop in 2015. According to the results, the hybrids with potential for using directly as double hybrid and/or for lines extractions to obtain new hybrids were: F 2 DKB 390 x F 2 60XB14, F 2 JM2M90 x F 2 60XB14, F 2 IVF5-IVD8x F 2 60XB14, F 2 DKB 350 x F 2 60XB14, F 2 DKB 390 x F 2 AG 8088 and F 2 8F/9D x F 2 AG 8088